Clinical perspective on pain in multiple sclerosis. (April 2022) - Yilmazer, Cigdem; Lamers, Ilse; Solaro, Claudio; Feys, Peter
Pain is an important and frequent symptom in multiple sclerosis (MS), which leads to a low quality of life, increased disability level, and lack of employment and mental health. Recently, studies have shown increased interest in pain in MS and there is a growing evidence of its prevalence. However, the literature suffers from lack of experimental studies focusing on pain reduction. This topical review summarizes the current knowledge about pain in MS with its definitions, assessments, treatments and rehabilitation within a holistic perspective.